Lessons on developing animated modules to introduce the sustainable development goals in undergraduate global health pedagogy - Ezezika, Obidimma; Fatima, Kishif; Jarrah, Mona; Yogalingam, Umayangga; McKee, Mark; Sicchia, Suzanne (Frontiers in Education, 2024)
Storyline animations can be used as immersive academic tools to engage students’ learning experiences. Based on Kolb’s experiential learning theoretical framework, we produced and pilot-tested a new storyline animation encompassing the Sustainable Development Goals for undergraduate students in a health studies course and utilized student survey responses to gather their feedback. In this paper, we outline the design, implementation, and feedback from students, culminating in five key lessons. First, simplicity should be the goal. Second, segments should be short and accessible. Third, interposed questions, discussion forums, and varying storyline routes improve interactivity. Fourth, relatability, positionality, and empathy enhance learning and immersion. Fifth, supplementary materials can improve learning. Based on these findings, we offer recommendations across the five lessons to help educators overcome challenges and facilitate the implementation of similar pedagogical opportunities in their curricula.